Incorporación de la bonificación clientelar para los contratos de agencia, en el Código de Comercio - Macas Ordóñez., Alex Xavier (2020)
The present investigation that is presented under the thesis modality, refers to a legal problem that deserves to be transformed to solve and overcome the socio-legal problem that is identified in the Código de Comercio, which brought us as a novelty the inclusion of agency contracts establishing in Article 500 ibid "that the agents referred to in this title differ from the commercial agents referred to in the labor laws of the country, due to the fact that they exercise their activity on their own", and in this context do not they 2 can access the same benefits of workers under a dependency relationship; and framed in doctrinal elements, it is necessary to implement in Article 498 of the aforementioned Código de Comercio, a bonus per clientele when the agency contract is terminated for reasons not attributable to the agent.